Intellectual capital and profitability: A firm value approach in the European companies - Martins, M. M. (2022)
Over the last decades, the world economy arose from an industrial economy into a knowledge-based economy. In the new era of knowledge, intangible assets are seen as the most important assets, driving companies towards unexpected returns. Intangible assets are capable to generate future benefits, which are drivers for differentiation. Companies are no longer seen as a pure production function to be recognized in its structural complexity. Companies are seen as new age networks structured on their resources and capabilities, most of them embodied by employees. The profitability of companies in the knowledge age is increasingly related to human factors and less based on tangible elements. Thus, it is strongly related to intellectual capital and less to physical capital. The concept of intellectual capital has been widely discussed in recent years and there is no single definition of the concept. Sometimes we can observe some interdisciplinary around it. The purpose of this paper is to investigate the association between the degree of intangibility of European companies and the profitability, and the association between the degree of intangibility and the value of firms. Companies were ranked according its own capacity to develop and drive a knowledge intensive activity. Based on its intangibility, two groups of companies were extracted according its degree of intangibility. Sample was based on the 500 largest European companies, rated by the Financial Times 2014 classification. Data relates to 2013 economic year. Profitability was measured by the following ratios: return on assets, return on equity, return on employed capital, and return on sales. The most relevant results of the empirical study evidence a statistically significant association between intangibility and profitability. This assumption corroborates the principles stated on intangibles literature and related accounting standards.